Fractional Order Controller for Electric Drives Under Parameter Uncertainty: A Controller Performance Analysis - Mehmood, Chaudhry Arshad; Kavasseri, Rajesh G (Journal of Electrical Systems, 2014)
Robustness to parameter variations is an important factor that dictates control performance in electric drives. This paper explores the suitability of fractional order controllers in combating parametric variations that arise in electric drives. The controller design and performance is illustrated with indirect field oriented control for an induction motor. Using numerical simulations in MATLAB/Simulink, the control performance of the proposed controller is compared with a well tuned traditional PID controller when critical motor parameters are subject to parametric variations about their nominal values. The parametric variations are subject to change with the ambient environment and passage of operation time, but in simulations the parameters are varied using sudden (step) change. The step change in parameters generates the worst case scenario for the motor under indirect field oriented control. The simulation results are encouraging and indicate that fractional order controllers provide a promising alternative for the design of robust controllers in electric drives applications.